THE EFFECT OF JOB SATISFACTION AND WORK MOTIVATION ON MIDWIVES' PERFORMANCE IN MAGELANG REGENCY VILLAGE - Rini - Yuliati (Faculty of Psychology, Diponegoro University, 2025)
Referring to the Minimum Service Standards (SPM) achievement for Maternal and Child Health services in 2024, the coverage of the Maternal and Child Health programme in Magelang Regency has not yet fully reached the targets, such as the achievement of services for pregnant women with K6, namely pregnant women who undergo a minimum of six examinations with health personnel, the achievement of child health services, the achievement of health services for those of productive age, and family planning. One of the causes is the suboptimal performance of village midwives in carrying out their main duties as village midwives. This research aims to determine the effect of work motivation and job satisfaction on the performance of village midwives in Magelang Regency, both partially and simultaneously. The hypotheses include the positive influence of work motivation, job satisfaction, as well as the simultaneous influence of both on performance.The research subjects are 125 active village midwives in the community health centres (puskesmas) of Magelang Regency in 2025. Performance data were taken from the Minimum Service Standards (SPM) achievement, while work motivation and job satisfaction were collected through questionnaires. The study employed purposive sampling techniques and multiple linear regression analysis. The results show that work motivation and job satisfaction do not have a significant effect on performance, either partially or simultaneously. Additional ANOVA analysis revealed a significant effect of educational factors on performance, as well as a correlation between job satisfaction and elderly health services as a performance indicator. These findings indicate that work motivation and job satisfaction are not dominant factors in the performance of village midwives.